Association between periodontal diseases and systemic illnesses: A survey among internal medicine residents in Nigeria - Kehinde A. Umeizudike; Sandra O. Iwuala; Obianuju B. Ozoh; Patricia O. Ayanbadejo; Olufemi A. Fasanmade (Elsevier, 2016)
Objective: To assess internal medicine residents' knowledge of associations between periodontal disease and systemic illnesses, and attitudes toward patients' periodontal health. Methods: A cross-sectional survey using a self-administered questionnaire was conducted among internal medicine residents attending the Faculty of Internal Medicine 2014 Update Course organized by the National Postgraduate Medical College of Nigeria. Participants came from all over the country. Data on respondents' demographic characteristics, periodontal disease knowledge, knowledge of associations between periodontal disease and systemic illnesses, and attitudes toward patients' periodontal health were collected. Data were analyzed using Epi INFO software. The Pearson chi square test was used to measure significant association between categorical variables such as the knowledge of periodontal disease and gender, age group and designation of the participants (p ⩽ 0.05). Results: Of 150 questionnaires distributed, 123 were returned (82% response rate); 109 questionnaires were completed properly and included in the analysis. The most common source of residents' information on oral health was television (59.4%). Only 11.2% of respondents were aware that gingival bleeding was the earliest sign of periodontal disease. Respondents correctly identified periodontal disease as a risk factor for coronary heart disease (45.9%), stroke (43.5%), hospital-acquired pneumonia (53.2%), diabetes mellitus (13.8%), and preterm birth (11%). Increased age (p = 0.032) and male gender (p = 0.022) were associated significantly with knowledge of periodontal disease as a risk factor for stroke. Higher designation (p = 0.002) and longer duration in residency training (p = 0.004) were associated significantly with knowledge of periodontal disease as risk factor for peripheral arterial disease. The majority (90.9%) of respondents had positive attitudes toward the referral of their patients for regular periodontal care. Conclusions: Knowledge of periodontal disease as a risk factor for systemic illnesses among medical residents in Nigeria is inadequate. These relationships should be emphasized in continuing medical education courses. Keywords: Knowledge, Periodontal disease, Systemic illnesses, Internal medicine residents, Nigeria